Experimental study on seed-filling performance of maize bowl-tray precision seeder - Mao, Xin; Yi, Shujuan; Tao, Guixiang; Yang, Li; Liu, Haiyan; Ma, Yongcai (International Journal of Agricultural and Biological Engineering, 2015)
According to the requirement of assorted maize transplanting machine, a maize bud-seed precise sowing device was presented for use in cold areas. Experiments were performed to optimise the parameters of a maize bowl-tray precise seeder to improve the seed-filling performance. When the diameter of brush seed wheel was 78 mm, the clearance of brushing seed was 3 mm, with the maize varieties Demeiya 1, the moisture content about 40%, the depth of shaped hole 6 mm, the two major factors, the diameter of shaped hole and the velocity of seed box, were tested at five levels for each factor using the orthogonal rotational regression experiment. The effects on the single-seed rate, multi-seed rate, empty-seed rate, broken-bud rate and damage rate were investigated. The test results indicated that the factors affecting the single-seed rate and the multi-seed rate were the diameters of shaped hole and the velocity of seeds box, and the factor affecting the empty-seed rate was primarily the diameter of shaped hole. This study determined the optimal parameters, and verified the results, which provide the basis for the design and performance improvement of the maize bud-seed bowl-tray precision seeder.Keywords: bowl-tray precision seeder, maize bud-seeds, seed-filling performance, orthogonal rotary regression experimentDOI: 10.3965/j.ijabe.20150802.1809